PREVALENCE OF MALARIA: KNOWLEDGE, ATTITUDE AND CULTURAL PRACTICES OF PREGNANT WOMEN IN KATSINA METROPOLIS, NIGERIA - J. A., Bawa,; T., Auta,; S., Liadi, (European Scientific Journal, ESJ, 2014)
A study on Malaria in Pregnancy was carried out in Katsina Metropolis. A total of four hundred and eight (408) pregnant women were interviewed and administered questionnaires. Blood samples from each of the interviewed subjects were collected to make thin and thick smears. A total of 149 samples of the blood were found to be infected with Plasmodium corresponding to prevalence 36.5%. Only one type of specie, Plasmodium falciparum was encountered during the study. Distribution of infection in the trimester was highest in the 1st trimester (43.5%) and among those with nonformal education (75.0%), but age group of 19 years has 45.7% and health workers with 100%. A high percentage of the respondents (93.4%) attributed malaria infection to mosquito bites. Knowledge on mode of transmission of malaria varies considerably among age groups, different educational level and social status. A low percentage (3.7%) of the subject respondents was asymptomatic while a higher percentage (75.2%) showed fever as a major symptom of malaria. This varies gradually among different age, gravids and trimester groups. About 2.0% mostly full house wives (3.1%) do not take any preventive measure of malaria, while a high percentage of 79.2% mostly teachers with 100% sleep under mosquito net as their preventive measure (P > 0.05). Among the respondents (20.8%) who did not sleep under mosquito nets, 8.6% of them have insufficient/no mosquito net, 2.4% restrict the infection to weather fluctuation and 0.5% attributed malaria to rainy season.